Autoalienação do trabalho e o trabalho docente em pós-graduação stricto sensu no PPGED/UFS - Santana, João Paulo Dória de (2014)
This research report aims to analyze the connections and determinations between self-alienation of work and the teaching work of the teacher - researcher in post-graduate courses stricto sensu, in particular the Federal University of Sergipe. We have used the historical - dialectic materialism as an explanatory basis, the research method and exposure. Our empirical sources were the annual reports of the Federal University of Sergipe, from the years 2004 to 2012; interviews with teachers - researchers associated to the teaching body of the Master´s and Doctorate PPGED, regularly tied to their respective departments and CAPES indicators books of teaching production PPGED between the years 2004 and 2012. We hypothesized that as the legal order proposed for the Brazilian public universities in recent years at the graduate level and post-graduate, we point to a specific process, resulting self-alienation of work, namely, the alienation of the teaching work of teacher - researcher, manifesting through casualization and intensification of their work. Through the analysis of our empirical and theoretical sources, pointed out that the expansion of the UFS (increase of 209% in enrollment) did not come accompanied by a proportional increase in the teaching staff (76%), which resulted in an increased ratio of teachers x student, as well as a reduction (31.6%) in the number of administrative staff by teaching functions in office. By analyzing the interviews, we reaffirm our hypothesis that casualization and intensification are expressions of alienation of teaching work, which also express themselves in teachers´ relationships with the political and impositions the federal government to universities. The long working hours which exceed the time and institutional spaces, the precarious working conditions, in addition to internal conflicts, mediated by power relations or |status| characterize the specificity of the alienation of teaching work.